2021
DOI: 10.1101/2021.09.29.462355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotypic plasticity, life cycles, and the evolutionary transition to multicellularity

Abstract: Understanding the evolutionary transition to multicellularity is a key problem in evolutionary biology (1,2). While around 25 independent instances of the evolution of multicellular existence are known across the tree of life (3), the ecological conditions that drive such transformations are not well understood. The first known transition to multicellularity occurred approximately 2.5 billion years ago in cyanobacteria (4,5,6), and today's cyanobacteria are characterized by an enormous morphological diversity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Before an ETI starts, the unicellular ancestors have been selected for traits that optimise growth rate in a unicellular environment under the constraints of their genetic constitution (‘Tradeoff-optimal particle phenotype’; blue disk in Figure 8 ). Then, a mutation (e.g., loss of the transcription factor ACE2, resulting in snowflake-shaped yeast clusters; see Ratcliff et al, 2015 ), a plastic change in phenotype (e.g., filament formation under low population densities in cyanobacteria; see Tang et al, 2022 ), a change in the structure of the environment (as in the ecological scaffolding model for the origin of multicellularity; see Black et al, 2020 ), or even a combination of several factors (‘wrinkly spreader’ mats arising by mutation and ecological scaffolding; see Hammerschmidt et al, 2014 ) promote the formation of collectives ( Figure 8 ). Multicellular collectives define a new environment where the optimal trait values are potentially different.…”
Section: Resultsmentioning
confidence: 99%
“…Before an ETI starts, the unicellular ancestors have been selected for traits that optimise growth rate in a unicellular environment under the constraints of their genetic constitution (‘Tradeoff-optimal particle phenotype’; blue disk in Figure 8 ). Then, a mutation (e.g., loss of the transcription factor ACE2, resulting in snowflake-shaped yeast clusters; see Ratcliff et al, 2015 ), a plastic change in phenotype (e.g., filament formation under low population densities in cyanobacteria; see Tang et al, 2022 ), a change in the structure of the environment (as in the ecological scaffolding model for the origin of multicellularity; see Black et al, 2020 ), or even a combination of several factors (‘wrinkly spreader’ mats arising by mutation and ecological scaffolding; see Hammerschmidt et al, 2014 ) promote the formation of collectives ( Figure 8 ). Multicellular collectives define a new environment where the optimal trait values are potentially different.…”
Section: Resultsmentioning
confidence: 99%
“…Before an ETI starts, the unicellular ancestors have been selected for traits that optimise growth rate in a unicellular environment under the constraints of their genetic constitution ("Tradeoff-Optimal particle phenotype"; blue disk in Figure 8). Then, a mutation (e.g., loss of the transcription factor ACE2, resulting in snowflake-shaped yeast clusters, Ratcliff et al, 2015), a plastic change in phenotype (e.g., filament formation under low population densities in cyanobacteria, Tang et al, 2021), a change in the structure of the environment (as in the ecological scaffolding model for the origin of multicellularity, Black et al, 2020) or even a combination of several factors ("wrinkly spreader" (WS) mats arising by mutation and ecological scaffolding, Hammerschmidt et al, 2014) promote the formation of collectives (Figure 8). Multicellular collectives define a new environment where the optimal trait values are potentially different.…”
Section: The Trait-based Approach In the Context Of Etismentioning
confidence: 99%
“…For example, phytoplankton 28 , cyanobacteria 29 , and Pseudomonads 30,31 can facultatively form multicellular clusters in response to predation. Moreover, a recent study has shown that changes in environmental salinity can induce multicellular clustering in marine cyanobacteria 32 . Such prevalence of facultative cell clustering across diverse unicellular taxa suggests that phenotypic plasticity may be an important force in the evolution of multicellularity.…”
Section: Introductionmentioning
confidence: 99%